Enhanced gold nanoparticle-tumor cell recognition by albumin multilayer coating - E. Achilli; C.Y. Flores; C.F. Temprana; S. del V. Alonso; M. Radrizzani; M. Grasselli (Elsevier, 2022)
Background: In a biological environment, nanoparticles are rapidly coated with serum proteins, which affects the NPs transport through biological medium, cellular uptake and response, all of which can impair therapeutic efficiency. Reduction of non-specific adsorption of proteins is mandatory to overcome this drawback. Aim: We propose to use albumin to prepare a multilayer coating of NPs to reduce the non-specific protein interactions in biological media. Materials & methods: Biohybrid NPs (bioHNPs) prepared by coating gold NPs with a multilayer of albumin and finally decorated with Bombesin-related peptides (BD-bioHNPs). Results: BioHNPs/biological media interaction was characterized by physicochemical and biological techniques under near-physiological conditions. A significant reduction of the Corona effect and enhanced in vitro uptake to PC-3 cells was demonstrated for BD-bioHNPs. Conclusion: This methodology to prepare decorated bioHNPs allows the preparation of 'stealth' NPs with improved cell targeting and the ability to avoid non-specific interactions with the biological media.